HUBUNGAN PEMBERIAN ASI EKSKLUSIF DENGAN PENURUNAN STUNTING PADA ANAK USIA 6-23 BULAN DI DESA SOSOR LONTUNG, KECAMATAN SIEMPAT NEMPU, KABUPATEN DAIRI TAHUN 2019 - Sinaga, Evanata Lina; Lubis, Rismahara; Siregar, Yusniar; Irianti, Evi (Colostrum Jurnal Kebidanan, 2019)
Stunting is a condition of failure to thrive in children under five due to chronic malnutrition. One cause of stunting is poor parenting patterns such as feeding in the first 2 years after birth. Exclusive breastfeeding is the best nutrition a baby receives in the first 6 months of life. The purpose of this study was to determine the relationship of exclusive breastfeeding with the decrease of stunting in children aged 6-23 months in Sosor Lontung Village, Siempat Nempu District, Dairi Regency. This study used a cross-sectional study design. The sample of this research was children aged 6-23 months as many as 39 people. Data collection was carried out by interview and measurement of children's length / height. Univariate and bivariate data analysis used Chi Square test with ?-value <0.05. Based on the bivariate analysis showed that there was a significant relationship between exclusive breastfeeding and the incidence of stunting with ?-value 0.037. The results showed the percentage of stunting in children aged 6-23 months was greater in children who were not given exclusive breastfeeding (50%) than those who received exclusive breastfeeding (17.65%). The results of bivariate analysis showed that there was a significant relationship between exclusive breastfeeding and the incidence of stunting with a value-value of 0.037. That is, exclusive breastfeeding can reduce the risk of stunting is getting smaller. It is hoped that all babies will receive exclusive breastfeeding so that the baby can grow optimally.